Chrystianizacja Gruzji według Historii Kościelnej Rufina z Akwilei - Niewiadomska, Magdalena (Saeculum Christianum. Pismo Historyczne, 2019)
The Church History by Rufinus of Aquileia is the oldest source concerning the Christianisation of Georgia, ancient Iberia. The author, drawing on information from the Iberian prince Bacurius, presents the events with a woman as their protagonist, a modest Roman Catholic. The example of her life and the miracles which through her intercession occurred in front of the pagan Iberians, are the direct cause of the people's acceptance of faith. The unusual, so active role of the woman, which is also confirmed by Georgian tradition, authenticates this valuable account. Rufinus bequeaths us the lacking information – despite many sources from that period – on how Christianity spread in the fourth century beyond the borders of the Roman Empire.